Identification of mitochondrial dysfunction in Hutchinson–Gilford progeria syndrome through use of stable isotope labeling with amino acids in cell culture - Rivera-Torres, José; Acín-Perez, Rebeca; Cabezas-Sánchez, Pablo; Osorio, Fernando G.; Gonzalez-Gómez, Cristina; Megias, Diego; Cámara, Carmen; López-Otín, Carlos; Enríquez, José Antonio; Luque-García, José L.; Andrés, Vicente (Journal of proteomics, 2013)
Hutchinson–Gilford progeria syndrome (HGPS) is a rare segmental premature aging disorder that recapitulates some biological and physical aspects of physiological aging. The disease is caused by a sporadic dominant mutation in the LMNA gene that leads to the expression of progerin, a mutant form of lamin A that lacks 50 amino acids and retains a toxic farnesyl modification in its carboxy-terminus. However, the mechanisms underlying cellular damage and senescence and accelerated aging in HGPS are incompletely understood. Here, we analyzed fibroblasts from healthy subjects and HGPS patients using SILAC (stable isotope labeling with amino acids in cell culture). We found in HGPS cells a marked downregulation of mitochondrial oxidative phosphorylation proteins accompanied by mitochondrial dysfunction, a process thought to provoke broad organ decline during normal aging. We also found mitochondrial dysfunction in fibroblasts from adult progeroid mice expressing progerin (LmnaG609G/G609G knock-in mice) or prelamin A (Zmpste24-null mice). Analysis of tissues from these mouse models revealed that the damaging effect of these proteins on mitochondrial function is time- and dose-dependent. Mitochondrial alterations were not observed in the brain, a tissue with extremely low progerin expression that seems to be unaffected in HGPS. Remarkably, mitochondrial function was restored in progeroid mouse fibroblasts treated with the isoprenylation inhibitors FTI-277 or pravastatin plus zoledronate, which are being tested in HGPS clinical trials. Our results suggest that mitochondrial dysfunction contributes to premature organ decline and aging in HGPS. Beyond its effects on progeria, prelamin A and progerin may also contribute to mitochondrial dysfunction and organ damage during normal aging, since these proteins are expressed in cells and tissues from non-HGPS individuals, most prominently at advanced ages. Mutations in LMNA or defective processing of prelamin A causes premature aging disorders, including Hutchinson–Gilford progeria syndrome (HGPS). Most HGPS patients carry in heterozygosis a de-novo point mutation (c.1824C>T: GGC>GGT; p.G608G) which causes the expression of the lamin A mutant protein called progerin. Despite the importance of progerin and prelamin A in accelerated aging, the underlying molecular mechanisms remain largely unknown. To tackle this question, we compared the proteome of skin-derived dermal fibroblast from HGPS patients and age-matched controls using quantitative stable isotope labeling with amino acids in cell culture (SILAC). Our results show a pronounced down-regulation of several components of the mitochondrial ATPase complex accompanied by up-regulation of some glycolytic enzymes. Accordingly, functional studies demonstrated mitochondrial dysfunction in HGPS fibroblasts. Moreover, our expression and functional studies using cellular and animal models confirmed that mitochondrial dysfunction is a feature of progeria which develops in a time- and dose-dependent manner. Finally, we demonstrate improved mitochondrial function in progeroid mouse cells treated with a combination of statins and aminobisphosphonates, two drugs that are being evaluated in ongoing HGPS clinical trials. Although further studies are needed to unravel the mechanisms through which progerin and prelamin A provoke mitochondrial abnormalities, our findings may pave the way to improved treatments of HGPS. These studies may also improve our knowledge of the mechanisms leading to mitochondrial dysfunction during normal aging, since both progerin and prelamin A have been found to accumulate during normal aging. [Display omitted] •SILAC analysis identifies multiple proteomic alterations in HGPS (progeria).•Mitochondrial dysfunction is a pathologic feature of HGPS.•Functional studies confirm mitochondrial defects in progeroid mouse models.•Statin+zoledronate ameliorate mitochondrial defects in HGPS mouse models.